Homocysteine levels in first-episode patients with psychiatric disorders - Fan, Ning; Zhao, Wenxuan; Yun, Yajun; Bai, Luyuan; An, Huimei; Zhang, Qi; Yan, Jiangling; Fan, Fengmei; Han, Xiaole; Yang, Fude (Frontiers in Psychiatry, 2024)
A high homocysteine (Hcy) level is a risk factor for schizophrenia, depression, and bipolar disorder. However, the role of hyperhomocysteinemia as either an independent factor or an auxiliary contributor to specific psychiatric symptoms or disorders remains unclear. This study aimed to examine Hcy levels in first-episode inpatients with psychotic symptoms and various psychiatric diseases to elucidate the association between Hcy levels and psychiatric disorders.This study enrolled 191 patients (aged 18-40 years) with psychiatric disorders. Seventy-five patients were diagnosed with schizophrenia, 48 with acute and transient psychotic disorders, 36 with manic episodes with psychosis, 32 with major depressive episodes with psychosis, and 56 healthy controls. Serum Hcy levels were measured using the enzyme cycle method. A Hcy concentration level of > 15 μmol/L was defined as hyperhomocysteinemia.Hcy levels were significantly higher in first-episode patients with psychiatric disorders compared to healthy controls (5.99 ± 3.60 vs. 19.78 ± 16.61 vs. 15.50 ± 9.08 vs. 20.00 ± 11.33 vs. 16.22 ± 12.06, F = 12.778, P < 0.001). Hcy levels were significantly higher in males with schizophrenia, acute and transient psychotic disorder, and major depressive disorder but not in mania [schizophrenia, (t = -4.727, P < 0.001); acute and transient psychotic disorders, (t = -3.389, P = 0.001); major depressive episode with psychosis, (t = -3.796, P < 0.001); manic episodes with psychosis, (t = -1.684, P = 0.101)]. However, serum Hcy levels were not significantly different among the psychiatric disorder groups (F = 0.139, P = 0.968). Multivariate linear regression showed that males had an increased risk for homocysteinemia. (95% CI = 8.192-15.370, P < 0.001).These results suggest that first-episode patients with psychiatric disorders have higher Hcy levels than in the general population, and men are at greater risk for psychiatric disorders. In conclusion, elevated Hcy levels may contribute to the pathogenesis of first-episode patients with psychotic symptoms.